A Level Playing Field? Media Constructions of Athletics, Genetics, and Race. Issue 1 (September 2015) - Hughey, Matthew W.; Goss, Devon R.
The link between black athleticism and biological determinism has been wrought with debate. With the domination of black athletics over white challengers—such as boxer Jack Johnson or sprinter Jessie Owens—some began to assert that blacks possessed a biological predisposition toward athletic excellence and that Darwinian winnowing during chattel slavery's harsh conditions magnified African American and West Indian athletic prowess. Despite biological and sociological evidence to the contrary, recent mainstream journalism has collectively advanced the proposition that black athletic success is the product of little more than genetic traits. In this article, we examine the events and ideologies employed to reify a media discourse of "black brawn vs. white brains." We demonstrate how such a thesis is empirically untenable. Through an examination of English-language newspaper articles ( N = 292) published in the decade immediately following the completion of human genome mapping (2003–2014), we examine contemporary media discourse surrounding athletics, genetics, and race. We demonstrate how mainstream media narratives construct and reinforce racial essentialism and provide a unique space for racist discourse in an age dominated by "postracial" and "color-blind" dialogue.